2021
DOI: 10.3390/electronicmat2020005
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes Induced by Heating in Sputtered NiO and Cr2O3 Thin Films as p-Type Transparent Conductive Electrodes

Abstract: NiO and Cr2O3 are transition metal oxides with a partially filled d electron band that supports p-type conduction. Both are transparent to the visible light due to optical absorption beginning at wavelengths below 0.4 μm and the creation of holes by metal vacancy defects. The defect and strain effects on the electronic characteristics of these materials need to be established. For this purpose, NiO and Cr2O3 thin films were deposited on unheated glass substrates by reactive DC sputtering from metallic targets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Hybridization of p-states of oxygen with unfilled d-states of transition metal can raise the valence band edge and make p-type doping possible in a way reported for p-type (Ir x Ga 1−x ) 2 O 3 solid solutions [12]. The advantage of Cr is the wider bandgap of α-Cr 2 O 3 compared to α-Ir 2 O 3 , allowing a bandgap increase of the solid solution [12,22,23], and the lower lattice mismatch of α-Cr 2 O 3 and α-Ga 2 O 3 compared to α-Ir 2 O 3 , facilitating easy solubility [10,12]. Growth of solid solutions of α-(Cr x Ga 1−x ) 2 O 3 has been reported for the case of mist CVD [19] but electrical properties have not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridization of p-states of oxygen with unfilled d-states of transition metal can raise the valence band edge and make p-type doping possible in a way reported for p-type (Ir x Ga 1−x ) 2 O 3 solid solutions [12]. The advantage of Cr is the wider bandgap of α-Cr 2 O 3 compared to α-Ir 2 O 3 , allowing a bandgap increase of the solid solution [12,22,23], and the lower lattice mismatch of α-Cr 2 O 3 and α-Ga 2 O 3 compared to α-Ir 2 O 3 , facilitating easy solubility [10,12]. Growth of solid solutions of α-(Cr x Ga 1−x ) 2 O 3 has been reported for the case of mist CVD [19] but electrical properties have not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…It can be grown on sapphire by magnetron sputtering with subsequent annealing [20,21] or by mist CVD [19]. The attractive feature of α-Cr 2 O 3 is that it is naturally p-type, due to Cr vacancies [22,23]. This opens possibilities for advantageously combining n-type α-Ga 2 O 3 and p-type α-Cr 2 O 3 to form a heterojunction.…”
Section: Introductionmentioning
confidence: 99%
“…Its low toxicity and abundance in nature make it an environmental-friendly alternative of other functional materials. 1 Therefore, recent studies have demonstrated the versatility of NiO as a valuable material for a wide range of uses, encompassing smart windows, 2 gas sensors, 3 solar cells, 4 ptype transparent conducting electrodes, 5 and electrochromic devices. 6 For many of these applications, NiO must be deposited as a thin film with a well-regulated microstructure.…”
mentioning
confidence: 99%